Faktor Internal, Kondisi Makroekonomi, dan Profitabilitas Perbankan di Indonesia: Analisis Dynamic Panel pada Bank Umum Konvensional - Dwi Ervyna Darma Putri; Gugum Mukdas Sudarjah; Nursaimatussaddiya Nursaimatussaddiya (Jurnal Riset Ilmu Ekonomi, 2026)
This study aims to analyze the determinants of profitability of conventional commercial banks in Indonesia by integrating bank-specific and macroeconomic factors within a dynamic panel framework. The study employs panel data from 62 conventional commercial banks supervised by the Financial Services Authority (OJK) over the period 2018–2024, resulting in 1,736 observations. Profitability is measured by Return on Assets (ROA), while bank-specific variables include Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO), and bank size (ASSET). Macroeconomic variables consist of inflation, BI Rate, and economic growth. The analysis applies the Dynamic Panel Generalized Method of Moments (GMM) estimator to address endogeneity issues and capture profitability persistence. The results reveal that bank profitability exhibits persistence, as indicated by the positive effect of lagged ROA on current profitability. CAR, NIM, NPL, LDR, and BI Rate positively affect profitability, whereas BOPO, bank size, inflation, and economic growth have negative effects. These findings suggest that operational efficiency, capital management, interest income generation, and macroeconomic stability are key determinants of banking profitability. The study provides important implications for regulators and bank managers in formulating policies and strategies to sustain profitability in the banking sector.